Peran Ketua Kelompok Tani dalam Penerapan Pupuk Organik pada Budidaya Cabai Rawit - Aliza Febrianti Mafinanik; Sri Subekti; Sofia Sofia; Lenny Widjayanthi (AGRITEXTS: Journal of Agricultural Extension, 2025)
The Role of Farmer Group Leader in the Application of Organic Fertilizer for Cayenne Pepper Cultivation. The application of organic fertilizer is strongly influenced by the direction and support of a leader, especially the head of a farmer group. This study aims to analyze the role of the farmer group leader in the application of organic fertilizer and identify obstacles faced by members. A descriptive qualitative research method was employed, utilizing observation, in-depth interviews, and documentation. Informants were determined purposively, consisting of 1 group leader, 13 members, and 1 Agricultural Extension Officer (PPL). Data analysis followed the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and conclusion drawing. Data validity was tested through source triangulation. The results show the group leader plays several roles. The liaison role involves bridging information between members, PPLs, farmers, and consumers. The leader’s role is evident in efforts to maintain group cohesion and manage the legality of organic fertilizer products. The monitoring role is carried out through overseeing and gathering information related to organic fertilizer. The dissemination role is carried out by providing information to members, while the spokesperson role is demonstrated by conveying the group’s needs to external parties. Additionally, the leader plays an entrepreneurial role by introducing innovations to members and is involved in problem-solving, resource allocation, and negotiation with PPLs, consumers, and local government. The obstacles faced by members include natural factors such as rain that hinders drying of raw materials, lack of drying equipment, limited member understanding, and limited availability of raw materials.